2003
DOI: 10.1080/714044482
|View full text |Cite
|
Sign up to set email alerts
|

Rearrangement Patterns of JC Virus Noncoding Control Region from Different Biological Samples

Abstract: The JC virus (JCV) is generally considered the etiological agent of progressive multifocal leukoencephalopathy (PML), a demyelinating brain illness, often associated with immunosuppression and significantly frequent in acquired immunodeficiency syndrome (AIDS) patients. The primary infection by JCV is usually asymptomatic and the virus can remain in a latent status in the kidney. As a consequence of immunological alterations of the host, the virus can show a genetic variability in the noncoding control region … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 0 publications
0
21
1
Order By: Relevance
“…Like BK virus, JC transcriptional control region variants could alter viral tissue tropism and increase pathogenic capability, even if the genomic structures isolated from urine samples are highly conserved in healthy and immunocompromised individuals and they always appear very similar to that of the archetype [Vaz et al, 2000;Pietropaolo et al, 2003]. Finally it is suggested that different genotypes of JC virus would act differently in immunocompromised individuals as in the case of progressive multifocal leukoencephalopathy .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Like BK virus, JC transcriptional control region variants could alter viral tissue tropism and increase pathogenic capability, even if the genomic structures isolated from urine samples are highly conserved in healthy and immunocompromised individuals and they always appear very similar to that of the archetype [Vaz et al, 2000;Pietropaolo et al, 2003]. Finally it is suggested that different genotypes of JC virus would act differently in immunocompromised individuals as in the case of progressive multifocal leukoencephalopathy .…”
Section: Discussionmentioning
confidence: 96%
“…Like BK virus, deletion and enhancement process could give rise to more active variants with altered tissue tropism and pathogenic capability [Vaz et al, 2000;Pietropaolo et al, 2003;Mischitelli et al, 2005]. The analysis of the viral protein 1 gene allowed to distinguish eight major genotypes and numerous subtypes of JC virus [Kmieciak et al, 2008].…”
Section: Introductionmentioning
confidence: 99%
“…β-Globin-positive samples were amplified in a GeneAmp® PCR System 9700 (PerkinElmer Cetus, Emeryville, CA), and all assays included positive (purified recombinant plasmid DNA) and negative (all the PCR components except the template) controls to exclude false-positive and false-negative results (Kwok and Higuchi 1989). Nested-PCR employed two pairs of primers that anneal to the invariant regions flanking the NCCR of JCV (Pietropaolo et al 2003). Primers BKTT1 (5′-AAG GTC CAT GAG CTC CAT GGA TTC TTC C-3′) and BKTT2 (5′-CTA GGT CCC CCA AAA GTG CTA GAGCAG C-3′) amplified a 724-bp DNA fragment in JCV (Mad-1) (Flaegstad et al 1991).…”
Section: Jcv Nccr Pcrmentioning
confidence: 99%
“…β-Globin PCR was performed on extracted DNA to assess the efficacy of nucleid acid extraction (Saiki et al 1985). General precautions, conditions for PCR analysis, and nested-PCR procedures were performed as published (Pietropaolo et al 2003). β-Globin-positive samples were amplified in a GeneAmp® PCR System 9700 (PerkinElmer Cetus, Emeryville, CA), and all assays included positive (purified recombinant plasmid DNA) and negative (all the PCR components except the template) controls to exclude false-positive and false-negative results (Kwok and Higuchi 1989).…”
Section: Jcv Nccr Pcrmentioning
confidence: 99%
“…2,3 The mechanism leading to PML is believed to include lethal infection of glia in the brain of the afflicted individual leading to severe demyelination and brain necrosis. Concerns regarding PML became more prominent when it was recognized that an increased number of PML cases occur in patients treated for autoimmune diseases with certain immunoregulatory agents, including natalizumab, rituximab, efalizumab and mycophenolate mofetil.…”
Section: Introductionmentioning
confidence: 99%